Everyday sports injuries. (New York : DK Publishing, 2019)
More people than ever before are regularly taking part in recreational sports, often gaining enormous health benefits from their chosen activity. But sports also carry the risk of injury, and each year there are millions of sports injuries in the US alone. Featuring more than 150 step-by- step exercise routines for recovery after injury, improving strength and performance, and reducing risk of injury, Everyday Sports Injuries is a practical guide to recognizing, treating, and preventing injury, with the goal of getting back in action as soon as possible.
Sports in profile -- Sports injuries -- Treatment & rehabilitation.
Includes index.
Keywords: SPORTS MEDICINE